PENGARUH LITERASI KEUANGAN, EFIKASI KEUANGAN, DAN FAKTOR DEMOGRAFI TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI (STUDI KASUS PADA MAHASISWA MAGISTER MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS ANDALAS PADANG) - Wilantika Waskito Putri, Masyhuri Hamidi (Departemen Manajemen, 2019)
The basis of investment decisions consists of the expected rate of return, the level of risk, and the relationship between return and risk. This research is to measure how the influence of financial literacy, financial efficacy and demographic factors on investment decisions. Case study on MM Unand Padang students. The sampling technique is using the proposive sampling method. Where the researcher determines the sampling by specifying specific characteristics that are in accordance with the objectives of the study so that it is expected to answer the research problems. Respondents were taken as samples listen to the criteria: Students who are active from 2018 B class morning, night and Friday-Saturday to 2016 B at the Faculty of Economics, Master of Management, Andalas University, Padang, have personal or work income. The net of samples is 200 MM Unand Padang students. Data were analyzed through by smart PLS. The results show that Financial Literacy has a positive and significant effect on investment decision making in MM Faculty of Economics Unand Padang Students. Financial Efficacy has a positive and significant effect on investment decision making at MM Faculty of Economics Unand Padang Students. And Demographic factors do not have a significant effect on investment decision making at MM Faculty of Economics Unand Padang students. Keywords : Financial Literacy, Financial Efficacy, Demographic Factors, Investment Decisions